Efficacy and safety of hormone therapies for treating adenomyosis-associated pelvic pain: a systematic review and network meta-analysis of randomized controlled trials - Etrusco, Andrea; Agrifoglio, Vittorio; D’Amato, Antonio; Chiantera, Vito; Laganà, Antonio Simone; Haydamous, Joe; Cobellis, Luigi; De Franciscis, Pasquale; Vannuccini, Silvia; Krentel, Harald; Naem, Antoine; Riemma, Gaetano (Frontiers in Endocrinology, 2025)
BackgroundTo date, there are no clear guidelines available on the treatment of adenomyosis-associated pelvic pain (AAPP); however, numerous hormonal treatments (HTs) are currently being used off-label. We conducted a systematic review and network metanalysis with the aim of assessing the efficacy and safety of HTs to reduce AAPP and ranking the available options.MethodsMEDLINE, LILACS, EMBASE, Scielo.br, PROSPERO, Cochrane Library, conference proceedings, and international registries were searched with no time, region, or language restrictions. Randomized controlled trials that analyzed AAPP in women undergoing HTs were deemed suitable.ResultsSix studies (563 women affected by adenomyosis) were included. At 3 months, women who received a placebo or a levonorgestrel-based intrauterine system (LNG-IUS) experienced more AAPP than those who received dienogest [mean difference of visual analog scale (VAS) pain scores (MD) 4.10 (95% CI 0.49 to 7.71); high evidence; MD 3.05 (95% CI 0.45 to 5.65); high evidence]. At 6 months, women who received dienogest experienced significantly less AAPP compared to those who received combined oral contraceptives [MD -2.85 (95% CI -5.30 to -0.39); moderate evidence], while the prevalence of AAPP was higher among those who received a LNG-IUS than those who received dienogest [MD 1.79 (95% CI 0.06 to 3.53); low evidence].ConclusionDienogest seems to be the most effective HT for AAPP. However, although rare, it is also related to more adverse effects compared to other HTs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024535472.